Modernisasi dan Sekularasi Pemikiran Islam di Indonesia - Silaen, Putri Alisia; Huda, Khoirul; Berutu, Lolo Ate Karina; Albani, Muhammad (Jayapangus Press, 2024)
The two key ideas in the evolution of Islamic thought in Indonesia are modernization and secularization. Modernization is an effort to keep Islamic teachings up-to-date and relevant to the changing times, while secularization is the division of religion and state affairs. The purpose of this study is to analyze how modernization and secularization have influenced Islamic thought in Indonesia. The research method used is qualitative with literature study. Primary data sources used are books (especially recommended for scientific work), recognized scientific publications, and student research findings in various formats, including theses, dissertations, practicum reports, and so on. Meanwhile, secondary data sources are obtained through previous research that has been carried out by previous research. The data analysis technique used is by data reduction which aims to conclude the results of the entire study. The results of the study show: First, if modernization and secularization have brought significant changes in Islamic thought in Indonesia, it shows that modernization encourages Muslims to adopt a rational mindset and be able to adapt to the progress of the times. Meanwhile, secularization helps Muslims in Indonesia to separate religious affairs from politics, thus allowing them to contribute more effectively to the development of the country. Second, modernization brings significant social changes, including changes in social structures, behavior patterns, and social interactions. Social change can occur suddenly or gradually, involving the active participation of community members. Globalization accelerates the modernization process by spreading ideas and cultures from Western countries to the rest of the world. Third, the relationship between Islam, modernization, and secularization is a complex and ever-evolving phenomenon, with diverse views and interpretations from various figures and thinkers.